Evaluating Indonesia's De-Radicalization Program: A Non-Punitive Approach to Countering Terrorism - Syarif Saddam Rivanie; Dian Anggraece Sigit Parawansa; Toetik Rahayuningsih; Ulil Amri; Ismail Iskandar; Afif Muhni; Akhmad Afif Athaullah; Muhammad Chafidz Ali Wafa (Faculty of Law, Universitas Pekalongan, 2025)
The most significant bombing incident in Indonesia was in Bali in 2002, resulting in the deaths of 202 individuals. After the bombing attack, Indonesia enacted Law Number 15 of 2003 about the Eradication of Criminal Acts of Terrorism. This Law exclusively governs criminal consequences, omitting other forms of penalties expressly targeting offenders of terrorism. The objective of this research is to identify alternative forms of sanctions that may be imposed on future perpetrators of terrorism. This research employs a normative methodology, utilizing both primary and secondary materials about legal rules concerning the eradication of terrorist criminal activities.Furthermore, it employs many legal methodologies, specifically the statutory and conceptual approaches. The findings indicated that deradicalization in Indonesia is critically necessary through the imposition of sanctions that must be enforced on terrorists in the future. Current deradicalization is not a punitive measure imposed on terrorists; instead, it seeks to eradicate their radical ideologies.